Biological aspects of red mite on tomato plants - Moraes, Gilberto J. de; Leite Filho, Antônio S. (Pesquisa Agropecuaria Brasileira, 2014)
Some biological aspects of Tetranychus evansi Baker & Pritchard, including the duration of young stages and reproductive capacity, were studied under laboratory conditions, using tomato var. Rossol as host plant. The durations of egg, larva, protonymph and deutonymph stages were of 4.8, 2.6, 2.4 and 3.2 days, respectively, corresponding to a total duration of approximately thirteen days from egg to adult for both saxes. The highest oviposition levels were attained from the fourth to the tenth day, approximately. An average of 105.7 eggs were laid during the whole oviposition period. Probably, the utilization of median or basal instead of apical leaves, as substrate, would have resulted in shorter life cycle and a higher total oviposition than what was obtained in this study.